A Simple Non-invasive Method to Predict Mitral Valve Geometric Orifice Area Following And Edge to Edge Repair - Gaillard, Emmanuel; Kadem, Lyes; Durand, Louis-Gilles (CMBES Proceedings, 2010)
Introduction. The edge to edge repair (EtER) technique consists of anchoring the free edge of the diseased leaflet of the mitral valve to the corresponding edge of the opposing leaflet. When the middle sections of the leaflets are sutured, a “double-orifice” mitral valve is artificially created. The main consequence of this technique is that mitral valve geometric orifice area (MGOA) is sensibly reduced and a functional mitral stenosis might be created. The purpose of this study was to determine mathematically the MGOA with a simple non-invasive formula following an EtER. Methods. To determine the MGOA following an EtER, we used the Lemniscate of Bernoulli. The Lemniscate has a shape similar to the “double-orifice” EtER. The area demarcated by the Lemniscates is given by the following simple equation: MGOA following “Double-Orifice” EtER = [Maximal Mitral Valve Diameter Before “Double-Orifice” EtER / 2]² + [(Maximal Mitral Valve Diameter Before “Double-Orifice” EtER / 2) – (Location of the Suture)]² Results and discussion. We showed that the reduction in MGOA following EtER was more dramatic for mitral valves with small initial MGOA. For example, a centered suture reduced the MGOA by 54.9% for an initial MGOA of 6.41 cm² whereas reduction reached up to 73.5% for an initial MGOA of 3.77 cm². Conclusions. We showed that, even if the “double-orifice” EtER technique seems to be an effective method to correct mitral regurgitation, the significant reduction of mitral valve area can become a problem for the patient. Finally, this simple mathematical model could be helpful for clinicians to determine the MGOA reduction after EtER.